Bidirectional mix recipes communication: an IoT solution (2022)
This prototype system eliminates the manual processes that are part of the process of loading and unloading mix recipes. For this, internet-enabled devices are connected to the mixing machine's system. Which act as a bridge for uploading and downloading the data of the mix recipes with the server.